Biomarkers of Exposure Among "Dual Users" of Tobacco Cigarettes and Electronic Cigarettes in Canada - Czoli, Christine D; Fong, Geoffrey T; Goniewicz, Maciej L; Hammond, David (Nicotine & tobacco research, 2019)
"Dual use" refers to the concurrent use of tobacco cigarettes (smoking) and electronic cigarettes (e-cigarettes; vaping). Although dual use is common among e-cigarette users, there is little evidence regarding biomarkers of exposure among dual users and how these change under different conditions of product use. A nonblinded within-subjects crossover experiment was conducted with adult daily dual users (n = 48) in Ontario, Canada. Participants completed three consecutive 7-day periods in which the use of tobacco cigarettes and e-cigarettes was experimentally manipulated, resulting in four study conditions: Dual use, Tobacco cigarette use, E-cigarette use, and No product use. Repeated measures models were used to examine changes in product use and biomarkers of exposure. Compared to dual use, cotinine remained stable when participants exclusively smoked (p = .524), but significantly decreased when they exclusively vaped (p = .027), despite significant increases in e-cigarette consumption (p = .001). Levels of biomarkers of exposure to toxicants, including carbon monoxide (CO), 1-hydroxypyrene (1-HOP), and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), were significantly lower when participants exclusively vaped than when they engaged in dual use (CO = -41%, p < .001; 1-HOP = -31%, p = .025; NNAL = -30%, p = .017). Similar findings were observed among participants abstaining from both products as compared to dual use (CO: -26%, p < .001; 1-HOP = -14% [ns]; NNAL = -35%, p = .016). In contrast, levels of biomarkers of exposure increased when participants exclusively smoked as compared to dual use (CO = +21%, p = .029; 1-HOP = +23%, p = .048; NNAL = +8% [ns]). Although dual use may reduce exposure to tobacco smoke constituents to some extent, abstaining from smoking is the most effective way to reduce such exposure. Public health authorities should clearly communicate the relative risk of e-cigarettes and tobacco cigarettes to the general public, focusing on two salient points: (1) e-cigarettes are not harmless, but they are less harmful than tobacco cigarettes; and (2) using e-cigarettes while smoking may not necessarily reduce health risks; therefore, consumers should stop smoking completely to maximize potential health benefits.